Tracking tumor heterogeneity and progression with near‐infrared II fluorophores. Issue 2 (16th March 2023) - Xin, Qi; Ma, Huizhen; Wang, Hao; Zhang, Xiao‐Dong
Abstract: Heterogeneous cells are the main feature of tumors with unique genetic and phenotypic characteristics, which can stimulate differentially the progression, metastasis, and drug resistance. Importantly, heterogeneity is pervasive in human malignant tumors, and identification of the degree of tumor heterogeneity in individual tumors and progression is a critical task for tumor treatment. However, current medical tests cannot meet these needs; in particular, the need for noninvasive visualization of single‐cell heterogeneity. Near‐infrared II (NIR‐II, 1000–1700 nm) imaging exhibits an exciting prospect for non‐invasive monitoring due to the high temporal‐spatial resolution. More importantly, NIR‐II imaging displays more extended tissue penetration depths and reduced tissue backgrounds because of the significantly lower photon scattering and tissue autofluorescence than traditional the near‐infrared I (NIR‐I) imaging. In this review, we summarize systematically the advances made in NIR‐II in tumor imaging, especially in the detection of tumor heterogeneity and progression as well as in tumor treatment. As a non‐invasive visual inspection modality, NIR‐II imaging shows promising prospects for understanding the differences in tumor heterogeneity and progression and is envisioned to have the potential to be used clinically. Abstract : The applications of NIR‐II Fluorophores in tracking the heterogeneity and progression of tumors. The advances in imaging the tumor heterogeneity, progression, and therapy are systematically summarized. As a non‐invasive visualized inspection modality, NIR‐II imaging further enables a deeper understanding of tumor pathophysiology and is envisioned for potential clinical translation.